Collective Bargaining and Perceived Fairness: Validating the Conceptual Structure - Cloutier, Julie; Denis, Pascale; Bilodeau, Henriette (Relations industrielles / Industrial Relations, 2012)
The aim of this study is to conceptualize the “perceived fairness in the context of collective bargaining” and empirically validate its internal structure. This concept refers to employees’ justice perceptions formed during the collective bargaining process (the process of determining the employees’ working conditions when they are unionized). Drawing on the organizational justice literature, we derive a conceptualization and formulate hypotheses regarding the convergent, discriminant and predictive validity of the concept’s dimensionality. The study was conducted among faculty at a Canadian university, where the collective bargaining process took nearly two years to complete. Using confirmatory factor analyses and hierarchical regressions, we find support for discriminant, convergent, and predictive validity. The results show that the new conceptualization includes eight distinct dimensions, combining the two sources of (in)justice (employer and union) and the four types of justice perceptions: procedural, distributive, relational (interpersonal) and informational justice. Indeed, employees clearly distinguish eight justice dimensions, which have a differential effect on their attitudes: trust in the employer and satisfaction with the union.Moreover, collective bargaining is an allocation process which encourages employees to participate actively. Because such participation might entails costs (energy, time, loss of money), employees are likely to form their justice perceptions based on not only elements from the structural model (Leventhal, 1980) and the process control model (Thibaut and Walker, 1975), but also two new justice elements: the usefulness of actions (the probability that actions force the employer to improve their offer to the expected level) and the profitability of actions (cost-benefits ratio).Opening the black box of collective bargaining through the concept of fairness is the first step in order to understanding the attitudinal and behavioural consequences of collective bargaining after employees have returned to work.